Sistem Monitoring Konsumsi Air Multi-Tenant Menggunakan Arduino dan Mobile Apps - Paskah Abraham; Djoni Haryadi Setiabudi; Resmana Lim (Jurnal Infra, 2019)
The manual water meter inspection procedure that is still being implemented to date has several disadvantages, one of which is error or fraud, both from the inspector (PDAM), and the water meter user who can manipulate the water meter. This is what triggers the creation of an Android-based mobile application equipped with Arduino and its components to be able to monitor water meters, which reflects the amount of water usage. Arduino devices and TCRT5000 sensors are installed on Itron Cyble water meters. The TCRT5000 sensor will work to calculate the number of rounds of measuring needles on the Itron Cyble water meter, and the calculation results from the sensors will be forwarded to the mobile application via the internet network. From the use of the application, the results can be shown the total water consumption of each water meter (multi-tenant) with the form of graph data presentation, and real-time on the mobile application. So, monitoring water consumption can be done through a mobile application.